Genitourinary tuberculosis manifesting as acute epididymo-orchitis: A report of two cases - (:unkn) unknown (My University, 2002)
Like tuberculous infection the overall incidence of genitourinary tuberculosis has increased in many countries during the recent years. Two cases of testicular tuberculosis manifesting as acute epididymo-orchitis are presented.
Keywords: Orchitis; Tuberculosis